Social Capital of Hafidzpreneur Students in Sustainable Sharia Economic Governance: A Maqāṣid Al-Sharīʻah Approach to SDG 8 In Indonesia - Unang Fauzi; Dimas Muhammad Hanief Arkaan -; Zikra Juninawan; Fahmi Alhadi (Profetika: Jurnal Studi Islam, 2026)
Objective: This study aims to analyse the contribution of social capital of hafidzpreneur students to sustainable sharia economic governance through the perspective of Maqāṣid al-Sharīʻah to support the achievement of SDG 8. Theoretical framework: The theoretical framework integrates social capital theory (beliefs, networks, and norms) with Maqāṣid al-Sharīʻah as the foundation of sustainable and SDG-oriented sharia economic governance 8. Literature review: Literature review was conducted through an integrative literature review of reputable national and international publications was conducted, including six articles from Profetika: Journal of Islamic Studies, on Islamic social capital, hafidzpreneur, Maqāṣid al-Sharīʻah, and SDG 8. Methods: The research uses a qualitative approach through integrative literature review, conceptual analysis, and content analysis of 324 Indonesian media news articles analysed by thematic synthesis. Results: The results of the study show that hafidzpreneur students form a distinctive Islamic social capital, where the spiritual discipline of tahfidz becomes the foundation for beliefs, socio-religious networks, and ethical norms in entrepreneurial activities. The social capital functions as a governance mechanism that reduces transaction costs, strengthens sharia compliance, and encourages ethical economic behaviour. Content analysis also showed that ḥifẓ al-māl was the most dominant goal of maqāṣid (69%), while 31% of the data simultaneously associated maqāṣid with SDG 8 indicators. Implications: The research findings serve as the basis for the development of tahfidz-based entrepreneurship policies and programs to strengthen sustainable sharia economic governance and support the implementation of SDG 8. Novelty: The novelty of the research lies in the integration of the concept of hafidzpreneur, social capital theory, and Maqāṣid al-Sharīʻah in building a sustainable sharia economic governance model oriented towards SDG 8.